Elementos para leer un palimpsesto: indígenas, caminos, piedras, mulas y caballos en Colombia (2006)
ABSTRACT: The text offers for discussion the necessary information in order to understand the manner in which indigenous technologies were integrated to new forms of production and commerce that were implemented with the arrival of the Spanish, paying special attention to the coexistence of routes paved with stone with the mules and horses necessary not only for greater flow of merchandise and means of production but also for the maintenance of the cultural patterns related to work, prestige and social hierarchies.